Neck Kaposiform haemangioendothelioma in a Fischer's lovebird (Agapornis fischeri). (June 2016) - Rossi, Giacomo; Galosi, Livio; Berardi, Sara; Piano, Maria Assunta; Robino, Patrizia; Rose, Timothy; Calabrò, Maria Luisa
Abstract: A six-year-old female Fischer's lovebird ( Agapornis fischeri ) presented at necropsy with a cutaneous mass on the neck, 3.5 cm in diameter, yielding and with blood content. Histopathological findings showed a neoplasm characterized by proliferation of vascular endothelial cells. The histology of the mass revealed a multinodular, focally infiltrating tumor. Deeper dermal nodules were made of spindle cells forming vascular slits reminiscent of the histology seen in Kaposi's sarcoma (KS). More superficially located dermal nodules consisted of small blood vessels, with histology resembling capillary hemangioma. The spindle cells and capillaries were strongly positive for Vimentin, endothelial cell marker CD31, and negative for sarcomeric α-smooth muscle actin (α-SMA). Intravascular platelet trapping and Periodic acid-Schiff (PAS)-positive hyaline globules were also observed. Differential diagnosis included Kaposi's sarcoma, capillary haemangioma, spindle cell haemangioendothelioma, and epithelioid haemangioendothelioma. Based on morphological and immunohistochemical findings, the tumor was diagnosed as a cutaneous Kaposiform haemangioendothelioma (KHE), a rare, low-grade malignant vascular neoplasm. Other organs showed no abnormalities. PCR amplifications, conducted using Kaposi's sarcoma-associated herpesvirus (KSHV)-specific primers and degenerate sets of primers designed to detect and characterize members of the Herpesviridae, on DNA extracted from tumor tissue and from whole blood failed to amplify any KSHV-related sequence. Moreover, no specific signal was obtained using primers for detection of psittacine herpesvirus, known to be linked to Pacheco's disease in parrots. To the best of our knowledge, this unusual case is the third report of KHE in a non-human animal species, the first described in a bird. Highlights: This vascular neoplasia is classified as "Kaposiform haemangioendothelioma". This is the third report of KHE in a non-human animal species, the first in a bird. Kaposi's Sarcoma Herpes virus-like sequences were not evidenced.